Addressing the Challenges of Novel Oncology and Hematology Treatments Across Sites of Care: Specialty Pharmacy Solutions. (April 2022) - Wyatt, Houston; Zuckerman, Autumn D.; Hughes, Mitchell E.; Arnall, Justin; Miller, Ryan
Background: The number of Food and Drug Administration (FDA) approvals for anticancer therapies has significantly increased in recent years, but these novel therapies are costly and present challenges to patients and providers. Many institutions have implemented health systems specialty pharmacies (HSSPs) to help patients and providers navigate financial and logistical barriers to treatment with oral anticancer therapies. Patients on oral anticancer therapy are often treated across multiple sites of care which can complicate the inpatient specialty medication initiation process. Health systems often limit inclusion of oral anticancer therapies for inpatient administration due to costs, however several new therapies necessitate admission for treatment initiation. Health systems are then faced with the challenge of starting costly oral anticancer therapy inpatient and ensuring continued access to therapy upon discharge. We describe the integrated HSSP multidisciplinary approach to this MUP including providers, inpatient and outpatient pharmacists, specialty and inpatient pharmacies, institutional procurement team, and the institutional pharmacy and therapeutics (P&T) committee to streamline this process. The HSSP multidisciplinary processes addresses a growing need for cancer patients to receive timely and affordable treatments across different sites of care. The healthcare team and P&T committee ensure the patient receives the most appropriate therapy while being conscious of health-system costs. The HSSP and procurement team ensure the patient can obtain and afford the medication. The implemented processes allows for direct communication and collaboration between different sites of care and this collaborative approach leads to optimal patient care.